[RETRACTED] Mampukah Kecerdasan Spiritual Memoderasi Hubungan Faktor Demografi terhadap Manajemen Keuangan Pribadi Mahasiswa? - Nurul Humairo; Indah Yuliana (Jurusan Ekonomi Pembangunan Fakultas Ekonomi Universitas Negeri Malang, 2020)
This article was retracted for violating Publication Ethics.This article was submitted in the journal Economic Education Vol. 13. No.1 March 2020 and also submitted to the Business and Management journal edition (ESENSI) of the Syarif Hidayatullah State Islamic University Jakarta on VOL 9, NO 2, 2019 (http://journal.uinjkt.ac.id/index.php/esensi / article / view / 13236)